2015
DOI: 10.1097/wnr.0000000000000404
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum levels of brain-derived neurotrophic factor in autism spectrum disorder

Abstract: The aim of this study was to investigate the potential role of brain-derived neurotrophic factor (BDNF) in children with autism spectrum disorders (ASD) by measuring serum circulating levels of BDNF as well as calcium and comparing them with age-matched and sex-matched normal controls. The study included 75 drug-naive ASD children and 75 age-sex-matched healthy children. The concentration of serum BDNF was determined using the enzyme-linked immunosorbent assay method at baseline. Clinical information was colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 23 publications
(25 reference statements)
2
24
0
Order By: Relevance
“…No significant difference was obtained for NGF (nerve growth factor) between the two strains (Hwang et al 2015). The upregulation of BDNF expression at an early developmental stage (in stark contrast to the BDNF signaling deficiency in later life of BTBR mice) is in line with clinical data showing increased plasma BDNF in children with ASD (Wang M. et al 2015). …”
Section: Altered Gene and Protein Expression In The Btbr Mousesupporting
confidence: 81%
“…No significant difference was obtained for NGF (nerve growth factor) between the two strains (Hwang et al 2015). The upregulation of BDNF expression at an early developmental stage (in stark contrast to the BDNF signaling deficiency in later life of BTBR mice) is in line with clinical data showing increased plasma BDNF in children with ASD (Wang M. et al 2015). …”
Section: Altered Gene and Protein Expression In The Btbr Mousesupporting
confidence: 81%
“…BDNF is involved in activity-dependent synaptic plasticity and there have been a number of studies linking BDNF with ASD (Armeanu, Mokkonen, & Crespi, 2017;Bryn et al, 2015;Kasarpalkar, Kothari, & Dave, 2014;Saghazadeh & Rezaei, 2017;Wang et al, 2015). Within the context of a genetic predisposition for ASD, coupled with environmental factors that result in over excitation of neurons, BDNF levels increase dramatically, resulting in the presence of a fatty coating around the neurons and megalencephaly (Merzenich, Van Vleet, Nahum, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The age of the subjects is a possible factor given the change of the BDNF levels over lifetime and the different developmental trajectories between the ASD subjects and the neurotypical counterparts . Our sample group was 30–42 months of age, that is slightly younger than that of Enstrom et al , Zhang et al , Wang et al and Meng et al that all found increased levels in children with ASD. However, as shown by our follow‐up results, BDNF levels seem to change significantly in ASD populations, even in short time in this critical young age.…”
Section: Discussionmentioning
confidence: 85%
“…Finally, after Nelson et al first report of higher BDNF levels in neonatal blood of children with ASD, multiple studies examined its serum levels with even the ambition to use them as a diagnostic or prognostic marker. Unfortunately, these studies have been yielding inconsistent results (Table ) . However, four recent published meta‐analyses (roughly using the same studies) all reported higher levels of BDNF in children with ASD, but also significant statistical heterogeneity across studies .…”
Section: Introductionmentioning
confidence: 99%